Dynamic nesting of Anaplasma marginale in the microbial communities of Rhipicephalus microplus - Piloto‐Sardiñas, Elianne; Abuin‐Denis, Lianet; Maitre, Apolline; Foucault‐Simonin, Angélique; Corona‐González, Belkis; Díaz‐Corona, Cristian; Roblejo‐Arias, Lisset; Mateos‐Hernández, Lourdes; Marrero‐Perera, Roxana; Obregon, Dasiel; Svobodová, Karolína; Wu‐Chuang, Alejandra; et al. (Ecology and evolution, 2024)
Interactions within the tick microbiome involving symbionts, commensals, and tick‐borne pathogens (TBPs) play a pivotal role in disease ecology. This study explored temporal changes in the microbiome of Rhipicephalus microplus, an important cattle tick vector, focusing on its interaction with Anaplasma marginale. To overcome limitations inherent in sampling methods relying on questing ticks, which may not consistently reflect pathogen presence due to variations in exposure to infected hosts in nature, our study focused on ticks fed on chronically infected cattle. This approach ensures continuous pathogen exposure, providing a more comprehensive understanding of the nesting patterns of A. marginale in the R. microplus microbiome. Using next‐generation sequencing, microbiome dynamics were characterized over 2 years, revealing significant shifts in diversity, composition, and abundance. Anaplasma marginale exhibited varying associations, with its increased abundance correlating with reduced microbial diversity. Co‐occurrence networks demonstrated Anaplasma's evolving role, transitioning from diverse connections to keystone taxa status. An integrative approach involving in silico node removal unveils the impact of Anaplasma on network stability, highlighting its role in conferring robustness to the microbial community. This study provides insights into the intricate interplay between the tick microbiome and A. marginale, shedding light on potential avenues for controlling bovine anaplasmosis through microbiome manipulation. This study investigates the dynamic interactions within the microbiome of the cattle tick Rhipicephalus microplus, emphasizing its relationship with the tick‐borne pathogen Anaplasma marginale. By analyzing ticks feeding on chronically infected cattle over a two‐year period using next‐generation sequencing, the research reveals significant fluctuations in microbiome diversity, composition, and abundance. The study elucidates the evolving role of A. marginale within the microbiome, highlighting its impact on microbial community stability and suggesting potential strategies for controlling bovine anaplasmosis through microbiome manipulation.